Integrasi Teknologi Informasi dalam Sistem Pembelajaran Pesantren: Studi tentang Adaptasi Santri di Era Literasi Digital - Siti Maulidyatul Jannah; Ahmad Halid (Jurnal Indonesia Kajian Pendidikan Islam, 2026)
Background: The development of information technology has driven significant changes in learning systems, including within pesantren, which are characterized by educational traditions rooted in classical scholarship and Islamic values. The integration of information technology has become an essential requirement for pesantren to remain relevant in the era of digital literacy, while simultaneously presenting challenges in preserving institutional identity and cultural heritage. Objective: This study aims to examine the integration of information technology within the pesantren learning system and to analyze the process by which santri adapt to these changes. Method: The research employs a qualitative approach using a literature review method based on critical analysis of relevant books, scholarly journals, and academic articles. Result: The findings indicate that information technology is utilized as a supportive learning tool such as digital media and online platforms, which contributes to improved access to knowledge and enhanced learning effectiveness among santri. However, the adaptation process occurs gradually and is influenced by levels of digital literacy, pesantren institutional policies, and guidance provided by educators. Conclusion: The study concludes that technological integration in pesantren is an adaptive process encompassing pedagogical, cultural, and ethical dimensions. Contribution: This research offers a conceptual contribution to the development of pesantren learning models grounded in digital literacy while remaining aligned with Islamic educational values.